Determinants of Contraceptive Use in Bangladesh (Ibrahim Medical College Journal, 2016)
Background: Bangladesh is experiencing a plateau phase in fertility decline after its dramatic reduction in early nineties. Aspects of contraceptive use dynamics have important influences on fertility. Methods: This study used data from the 2004 Bangladesh Demographic and Health Survey and applied Multinomial Logistic Regression model to examine the determinants of use of modern methods of contraception. Results: The results showed that individual level characteristics had strong influence on contraceptive use. These variables included educational level of the couples, autonomy of woman, male child preference, womans membership with an NGO, visit by family planning worker, region and type of residence. Conclusion: The analysis indicated that further increase of contraceptive prevalence rate to achieve decline in fertility level depended on the improvement of educational status of couples and as well as increase in societal value of girl child. It was evident that household visit by a family planning worker was a significant factor in contraceptive use. Influences of Muslim religion were found to be declining in the case of several methods of contraception use. NGOs could take this opportunity to advocate condom use among their credit clients, which would also benefit the country as a policy against sexually transmitted diseases and AIDS.Ibrahim Med. Coll. J. 2014; 8(2): 34-40